A2, M2, P2 aneurysms and beyond: results of treatment with pipeline embolization device in 65 patients. (23rd January 2019) - Primiani, Christopher T; Ren, Zeguang; Kan, Peter; Hanel, Ricardo; Pereira, Vitor Mendes; Lui, Wai Man; Goyal, Nitin; Elijovich, Lucas; Arthur, Adam S; Hasan, David M; Ortega-Gutierrez, Santiago; Samaniego, Edgar A; et al.
Abstract : Background: Intracranial aneurysms located in the distal vessels are rare and remain a challenge to treat through surgical or endovascular interventions. Objective: To describe a multicenter approach with flow diversion using the pipeline embolization device (PED) for treatment of distal intracranial aneurysms. Methods: Cases of distal intracranial aneurysms defined as starting on or beyond the A2 anterior cerebral artery, M2 middle cerebral artery, and P2 posterior cerebral artery segments were included in the final analysis. Results: 65 patients with distal aneurysms treated with the PED were analyzed. Median aneurysm size at the largest diameter was 7.0 mm, 60% were of a saccular morphology, and 9/65 (13.8%) patients presented in the setting of acute rupture. Angiographic follow-up data were available for 53 patients, with a median follow-up time of 6 months: 44/53 (83%) aneurysms showed complete obliteration, 7/53 (13.2%) showed reduced filling, and 2/53 (3%) showed persistent filling. There was no association between patient characteristics, including aneurysm size (P=0.36), parent vessel diameter (P=0.27), location (P=0.81), morphology (P=0.63), ruptured status on admission (P=0.57), or evidence of angiographic occlusion at the end of the embolization procedure (P=0.49). Clinical outcome data were available for 60/65 patients: 95% (57/60) had good clinical outcome (modified Rankin Scale score of 0–2) at 3 months. Conclusions: This large multicenter study of patients with A2, M2, and P2 distal aneurysms treated with the PED showed that flow diversion may be an effective treatment approach for this rare type of vascular pathology. The procedural compilation rate of 7.7% indicates the need for further studies as the flow diversion technology constantly evolves.